THE IMPORTANCE OF ENDOTHELIAL DYSFUNCTION IN THE DEVELOPMENT OF DISORDERS OF THE HEMOSTASIS SYSTEM IN PATIENTS WITH RHEUMATOID ARTHRITIS (Academicia Globe: Inderscience Research, 2023)
Patients with chronic inflamatory diseases manifest endothelial dysfunction, often early in the course of the disease.